Laboratory Evaluation of Sorptive Filtration Media Mixtures for Targeted Pollutant Removals from Simulated Stormwater - Prabhukumar, Giridhar (Water environment research : a research publication of the Water Environment Federation, 2015)
Urban stormwater pollutants including nutrients, trace metals, polycyclic aromatic hydrocarbons (PAHs), total suspended solids (TSS) and indicator microorganisms (E. coli) were the target pollutants in this study. Their simultaneous removal from synthetic stormwater using different sorptive media was investigated through laboratory-scale column experiments. The media considered for testing were calcite (C), sand (S), zeolite (Z) and iron filings (Fe(0)). These media are easily/commercially available, environmentally benign, long lasting (non-biodegradable), highly permeable and effective in removing multiple target pollutants. Based on individual media testing, three different mixed media compositions were selected (1) C-Z-S, (2) C-S-Fe(0) and (3) C-Z-S-Fe(0), for simultaneous removal of target pollutants using column experiments. The mixed media composition, C-Z-S-Fe(0) showed significantly better simultaneous removal of all the target pollutants as compared to the other two compositions. These compositions can be tailored to meet site-specific stormwater pollutant removal in a passive in-ground sorptive media filter